Fibril deformation under load of the rabbit Achilles tendon and medial collateral ligament femoral entheses. Issue 9 (25th April 2018) - Sevick, Johnathan L.; Abusara, Ziad; Andrews, Stephen H.; Xu, Minjia; Khurshid, Saad; Chatha, Jansher; Hart, David A.; Shrive, Nigel G.
ABSTRACT: Microscopic visualization under load of the region connecting ligaments/tendons to bone, the enthesis, has been performed previously; however, specific investigation of individual fibril deformation may add insight to such studies. Detailed visualization of fibril deformation would inform on the mechanical strategies employed by this tissue in connecting two mechanically disparate materials. Clinically, an improved understanding of enthesis mechanics may help guide future restorative efforts for torn or injured ligaments/tendons, where the enthesis is often a point of weakness. In this study, a custom ligament/tendon enthesis loading device was designed and built, a unique method of sample preparation was devised, and second harmonic and two‐photon fluorescence microscopy were used to capture the fibril‐level load response of the rabbit Achilles tendon and medial collateral ligament femoral entheses. A focus was given to investigation of the mechanical problem of fibril embedment. Resultant images indicate a rapid (occurring over approximately 60 μm) change in fibril orientation at the interface of ligament/tendon and calcified fibrocartilage early in the loading regime, before becoming relatively constant. Such a change in fibril angle helps confirm the materially graded region demonstrated by others, while, in this case, providing additional insight into fibril bending. We speculate that the scale of the mechanical problem (i.e., fibril diameters being on the order of 250 nm) allows fibrils to bend over the small (relative to the imaging field of view, but large relative to fibril diameter) distances observed; thus, potentially lessening required embedment lengths. Nevertheless, this behavior merits further investigation to be confirmed. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2506–2515, 2018.